Problem Solving Method In Improving Students' Critical Thinking Abilities In Social Studies Learning - Rachmat Panca Putera; Nurlaili Hidayatul Baiti; Anita Puspa Meilina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Enhancing students' critical thinking skills is a major challenge in Social Studies education in the 21st century. This study aims to explore the effectiveness of the problem-solving method in improving students' critical thinking skills within the context of Social Studies. Employing a qualitative approach with a library research design, this research analyzes various literature related to the application of the problem-solving method. Findings reveal that this method significantly enhances students' abilities to analyze information, formulate solutions, and connect theory with practice. However, challenges such as resource limitations and the need for teacher training can impact its effectiveness. The implications of this research suggest the need for intensive teacher training and systematic integration of the problem-solving method into the social studies curriculum to improve educational quality. Future research is recommended to explore different educational settings and additional method combinations to deepen understanding of problem-solving implementation in social studies education.